Analisis Akuntabilitas, Transparansi, dan Partisipasi Masyarakat dalam Pengelolaan Keuangan Dana Desa - Rina Sulistyowati; Rita Nataliawati (Owner : Riset dan Jurnal Akuntansi, 2022)
The study aims to analyze accountability, transparency and community participation in the financial management on the Mojoranu Village Fund. The data analysis technique uses descriptive qualitative techniques by reducing data, displaying data and drawing conclusions (verification). The results showed that the accountability of financial management of Mojoranu village funds was appropriate. Transparency in the management of Mojoranu's village funds has not been fully transparent, while community participation in development planning such as meetings has been good. Community participation in the implementation of development is good. Community participation in supervision is still lacking. While participation in the evaluation phase was quite good.